The impact of the review process in hypothesis generation tasks - Ismail, Zubaidah; Trotman, Ken T. (Accounting, Organizations and Society, 1995)
This paper examines the performance of auditors in generating hypotheses in an analytical review case both prior to and after review. It partitions two possible sources of gain from the review process, namely the discussion effect and the rank effect. The discussion effect compares review groups with and without discussion. The rank effect compares seniors and audit managers. The study found that the review process results in more plausible hypotheses being generated. Discussion within the review process between reviewer and reviewee was found to be one source of gain from the review process. While there was no difference in the performance of the senior and manager reviewers, managers completed the task in less time.